A Suggestion for a New E-Governance System in the Wheat Supply Chain Management - Dündar, Abdullah Oktay; Peker, Kenan; Tekin, Mahmut; Şahman, Mehmet Akif; Büber, Mustafa (PLUSBASE AKADEMİ ORGANİZASYON VE DANIŞMANLIK, 2016)
Previously in Turkey, there have been no information systems used by buyers and suppliers in the wheat supply process. In general, the supply process has previously been accomplished through personal meetings or through the stock market. After loading their wheat on vehicles, farmers take the wheat to potential buyers (e.g. flour mills, merchants, stock market, Agricultural Products Office [APO]). The buyers evaluate the wheat using laboratory facilities, or by observation, and offer a price to the farmers. If there is a deal, the sale is realized. If there is no deal, the farmers take the wheat to other potential buyers and follow the same process again. This leads to unnecessary transportation, and an unnecessary increase in costs. This study proposes a wheat supply e-governance system to eliminate unnecessary transportation, and create a new communication channel between buyers (flour mills as the end buyers) and suppliers (farmers). This system will enable a reduction in the length of the supply chain, building faster communication between the members of the supply network, and will reduce the costs of buying and carrying wheat.  In addition, the agricultural consultancy system will be operated more effectively, and farmers will be able to learn about their own analysis results from the system.
Keywords: Engineering; Mühendislik